Impact Of Educational Units Based On S.A.M.R Model On Students ' Cognitive Development And Learning Of Some Offensive Basketball Skills - Rasha Abbas Abdul Razzaq (Journal of Education and Sport Science, 2026)
This study aimed to develop educational units based on SAMR model, focusing on knowledge acquisition and some offensive basketball skills. It also aimed to identify impact of these units on the studied variables. The researcher employed an experimental design with two equivalent groups using pre- and post-tests. The study was conducted with 40 second-year students from College of Physical Education and Sports Sciences at Al-Mustansiriya University during the 2024-2025 academic year. The researcher selected offensive skills from the curriculum, including chest passes, high dribbles, and stationary shots. Based on these skills, the researcher assessed the students' knowledge acquisition. The educational units were implemented over eight weeks. After the implementation and data collection, the researcher drew several conclusions, the most important of which are: SAMR model The method used contributed positively to students gaining knowledge and learning to perform some offensive basketball skills , as well as the SAMR model . He may have surpassed the traditional method in terms of cognitive achievement and learned to perform some offensive basketball skills . Furthermore, the educational techniques employed in a structured and sequential manner through the SAMR model were utilized. It has contributed to making the learning process easier for students and acquiring knowledge more effectively.